Environmental interiors - Weale, Mary Jo.; Croake, James W.;Weale, W. Bruce (New York : Macmillan Publishing Company, 1982)
This book is a valuable addition to the published material available to both the beginning interior design student and the practicing professional who needs a current reference. This book will also be of value to the interested layperson.
Part One. The designed environment -- Part Two. The interior environment -- Part Three. The historical environment -- Part Four. Implementation technique.
Includes index.
Keywords: INTERIOR ARCHITECTURE